Challenges and prospects of plasmonic metasurfaces for photothermal catalysis - Mascaretti, Luca; Schirato, Andrea; Fornasiero, Paolo; Boltasseva, Alexandra; Shalaev, Vladimir M; Alabastri, Alessandro; Naldoni, Alberto (Nanophotonics (Berlin, Germany), 2022)
Solar-thermal technologies for converting chemicals using thermochemistry require extreme light concentration. Exploiting plasmonic nanostructures can dramatically increase the reaction rates by providing more efficient solar-to-heat conversion by broadband light absorption. Moreover, hot-carrier and local field enhancement effects can alter the reaction pathways. Such discoveries have boosted the field of photothermal catalysis, which aims at driving industrially-relevant chemical reactions using solar illumination rather than conventional heat sources. Nevertheless, only large arrays of plasmonic nano-units on a substrate, i.e., plasmonic metasurfaces, allow a quasi-unitary and broadband solar light absorption within a limited thickness (hundreds of nanometers) for practical applications. Through moderate light concentration (∼10 Suns), metasurfaces reach the same temperatures as conventional thermochemical reactors, or plasmonic nanoparticle bed reactors reach under ∼100 Suns. Plasmonic metasurfaces, however, have been mostly neglected so far for applications in the field of photothermal catalysis. In this Perspective, we discuss the potentialities of plasmonic metasurfaces in this emerging area of research. We present numerical simulations and experimental case studies illustrating how broadband absorption can be achieved within a limited thickness of these nanostructured materials. The approach highlights the synergy among different enhancement effects related to the ordered array of plasmonic units and the efficient heat transfer promoting faster dynamics than thicker structures (such as powdered catalysts). We foresee that plasmonic metasurfaces can play an important role in developing modular-like structures for the conversion of chemical feedstock into fuels without requiring extreme light concentrations. Customized metasurface-based systems could lead to small-scale and low-cost decentralized reactors instead of large-scale, infrastructure-intensive power plants.
Keywords: solar fuels; plasmonic metasurfaces; photothermal catalysis; gas phase; photocatalysis